Cost Effective Approach for In vitro Propagation of (Leptadenia reticulata Wight &Arn.) - A Threatened Plant of Medicinal Importance - Balasubramanya S3 and Anuradha M1,2, Sudipta K.M1, Kumara Swamy M2*, (Journal of Phytology, 2011)
The present study deals with the development of an efficient and simple protocol for high frequency in vitro regeneration of Leptadenia reticulata, a threatened medicinal plant. A range of cytokinins with different concentration and affect of various media have been investigated for multiple shoot induction using nodes, internodes, meristem as explants. The best response for multiplication was obtained in MS media supplemented with 0.25mg/l BA and 0.25mg/l Kn. B5 media efficiently proliferated callus. Among the all the explants tested only those of old axillary nodes showed positive morphogenetic response and readily developed healthy multiple shoots, where as the other explants such as young axillary nodes, apical meristem and internodes did not respond satisfactorily. Maximum numbers of roots were observed when the in vitro grown shoots were maintained on full strength MS media containing 2mg/l IBA followed by 200 mg/l activated charcoal. The cost of the media was reduced by using tap water and table sugar in the media. About 93% of the plants were successfully acclimatized in the field. Key words: Multiple shoot induction, Axillary nodes, In vitro regeneration, Asclepiadaceae Abbreviations: BA: 6-benzyladenine, IAA: Indole-3-aceticacid, IBA: Indole-3-butyric acid, Kn: Kinetin, NAA: α-naphthalene acetic acid, MS: Murashige&Skoog’s medium, SE.: Standard error Sudipta K.M et al. Cost Effective Approach for In vitro Propagation of (Leptadenia reticulata Wight &Arn.) - A Threatened Plant of Medicinal Importance. J Phytol 3/2 (2011) 72-77